1995
DOI: 10.1590/s0036-46651995000100012
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hepatitis C infection among Brazilian hemodialysis patients in Rio de Janeiro: a one-year follow-up study

Abstract: Nearly 400 hemodialysis patients treated at 5 different hemodialysis units in Rio de Janeiro were tested for one year for the presence of hepatitis C and B markers. During the same period, samples were also obtained from 35 continuous ambulatory peritoneal dialysis (CAPD) patients and from 242 health care workers. Depending on the hemodialysis unit studied, anti-HCV prevalence rates ranging from 47% to 82% (mean 65%) were detected. CAPD patients showed a lower prevalence of 17%. The prevalence of antibodies ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
1
8

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 17 publications
3
23
1
8
Order By: Relevance
“…As in other studies, we did not find association between the base disease and the frequency of infection by the hepatitis C virus [16,17].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As in other studies, we did not find association between the base disease and the frequency of infection by the hepatitis C virus [16,17].…”
Section: Discussionsupporting
confidence: 68%
“…Several projects performed in Brazil between 1992 and 2004 point a HCV frequency varying from 23.5% to 65% [7,[12][13][14][15][16]. Data from Santa Catarina State indicate the occurrence of the infection by HCV at the dialysis clinics in 33.4% [17].…”
Section: Discussionmentioning
confidence: 99%
“…This HBsAg prevalence was higher than those found in developed countries as Spain (2.2%) (López-Alcorocho et al 2001), Switzerland (1.6%) (Ambühl et al 2000), and the US (0.9%) (Tokars et al 2002). However, this rate was lower than those observed in other studies conduced before the implementation of improved methods for prevention and control of infection in Brazilian hemodialysis units (Cenderoglo Neto et al 1995, Vanderborght et al 1995. In fact, recently Teles et al (2002) reported a decline of the HBsAg prevalence from 12%, in 1995, to 5.8%, in 1999, among hemodialysis patients from Goiânia city.…”
Section: Discussionmentioning
confidence: 52%
“…Also, in this study, the prevalence declined to 2.4% in 2002 (data not shown). With reference to other Brazilian hemodialysis populations, HBsAg prevalence found in Central Brazil was lower than those observed in Tocantins (4%) (Souza et al 2003) and Santa Catarina (10%) in North and South regions, respectively, and also in Belo Horizonte (4.4%) (Busek et al 2002), Rio de Janeiro (11.1%) (Vanderborght et al 1995), and São Paulo (15.1%) (Cendoroglo Neto et al 1995) in Southeast of Brazil. However, these HBsAg prevalence rates were Length of time on hemodialysis < 1 year 1.0 1.0 1 a 3 years 1.1 (0.8-1.6) 0,9 (0.6-1.4) > 3 years 2.6 (1.8-3.7) 2.6 (1.7-4. higher than those found in developed countries as Switzerland (1.6%) (Ambuhl et al 2000) and the US (1%) (Finelli et al 2005).…”
mentioning
confidence: 87%